2020
DOI: 10.1152/japplphysiol.01077.2018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of testosterone suppression, hindlimb immobilization, and recovery on [3H]ouabain binding site content and Na+, K+-ATPase isoforms in rat soleus muscle

Abstract: We investigated the effects of testosterone suppression, hindlimb immobilization, and recovery on skeletal muscle Na+,K+-ATPase (NKA), measured via [3H]ouabain binding site content (OB) and NKA isoform abundances (α1–3, β1–2). Male rats underwent castration or sham surgery plus 7 days of rest, 10 days of unilateral immobilization (cast), and 14 days of recovery, with soleus muscles obtained at each time from cast and noncast legs. Testosterone reduction did not modify OB or NKA isoforms in nonimmobilized contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Murphy et al (2007) observed a higher muscle mRNA expression of the NKAα3 and β3 subunits for recreationally active males than females but not for either the total NKA content or maximally stimulated activity. A putative role of sex hormones, testosterone, and oestrogen in the regulation of NKA abundance has been shown in rat soleus muscle [ 46 ] and cardiomyocytes [ 47 ], respectively. Furthermore, the oestrogen receptor has been implicated in the regulation of dysadherin in multiple large-scale studies on cancer progression [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Murphy et al (2007) observed a higher muscle mRNA expression of the NKAα3 and β3 subunits for recreationally active males than females but not for either the total NKA content or maximally stimulated activity. A putative role of sex hormones, testosterone, and oestrogen in the regulation of NKA abundance has been shown in rat soleus muscle [ 46 ] and cardiomyocytes [ 47 ], respectively. Furthermore, the oestrogen receptor has been implicated in the regulation of dysadherin in multiple large-scale studies on cancer progression [ 48 ].…”
Section: Discussionmentioning
confidence: 99%